Relationship between Knowledge, Immunization Status and Exclusive Breastfeeding History with the Incidence of Sickness in Toddlers at Puskesmas Sindang Beliti Ilir, Rejang Lebong Regency, 2023 - Susilawati, Susilawati; Murwati, Murwati; Azissah, Danur (Universitas Dehasen Bengkulu, 2024)
ARI is an infectious disease of the airway which is anatomically distinguished from the upper airway starting from the nose to the pharynx and the lower airway starting from the larynx to the alveoli and their adnexa which occurs due to the invasion of infecting agents which results in an inflammatory reaction of the airway involved (Lantong, et al, 2016 Research Objectives known relationship of knowledge, This type of research is an analytical study using a cross-sectional design which is a research design by measuring or observing at the same time (once at a time) between risk factors / exposure and disease (Hidayat, 2012). All mothers of toddlers who visited the Sindang Beliti Ilir health center in 2022 amounted to 349 people. and the number of samples in this study were 78 respondents. The results of this study indicate that half of the respondents 39 (50.0%) had good knowledge, almost all respondents 71 (91. 0%) Complete basic immunization status, almost all respondents 71 (91.0%), There is a history of exclusive breastfeeding, Most respondents 66 (84.6%) No URI, There is a relationship between knowledge and the incidence of URI (p value 0.044), There is a relationship between immunization status and the incidence of URI (p value 0.000), There is a relationship between exclusive breastfeeding history and the incidence of ARI (p value 0.000) at the Sindang Beliti Ilir Health Center, Rejang Lebong Regency in 2023.It is recommended that the results of this study to the health center will more often provide education to mothers who have toddlers, especially factors that can cause the incidence of ARI.